The role of amelogenin during enamel crystallite growth and organization in vivo - Wright, J. Timothy (2011)
Amelogenin is critical for enamel formation and human AMELX gene mutations cause hypoplastic and/or hypomaturation enamel phenotypes. The Amelx null (AKO) mouse has a severe hypoplastic phenotype. This study evaluated the effect of amelogenin loss on enamel formation and crystallite morphology. Enamel from AKO and wild type (WT) mice was used. AKO mice were mated with transgenic mice expressing the most abundant known amelogenin isoform TgM180-87 to rescue (KOM180-87) the enamel crystallite phenotype. Molar enamel was embedded, sectioned with a diamond microtome and photographed using transmission electron microscopy. Crystallite sizes from multiple sections were measured using Image J. Crystallite mean thicknesses were (WT = 26 nm, AKO = 16 nm, KOm180-87 = 25 nm) and the mean widths were (WT = 96 nm, AKO = 59 nm, KOm180-87 = 85 nm). Despite a complete loss of amelogenin in AKO mice, a mineralized enamel layer with well-defined and organized crystallites forms. Enamel crystallites forming in the absence of amelogenin were reduced in thickness and width. For the first time we show that introduction of the m180 amelogenin isoform into the AKO mouse through crossbreeding rescues the crystallite phenotype. We conclude that amelogenin is essential for the development of normal crystallite size.